Design of a Web-Based Notary Order Application (SI-ON) to Improve the Quality of Banking Credit Services - Rahmi, Nurlaili; Kurniati, Kurniati; Sari, Diah Novita (Jurnal Sains Sosio Humaniora, 2025)
The notary ordering process in banking credit services is still largely conducted manually through separate communication channels, such as telephone calls, instant messaging applications, and electronic mail. This condition may lead to delays in information delivery, difficulties in monitoring work progress, and less integrated document management, which can affect the effectiveness of credit administration and service quality. This study aims to design a web-based Notary Ordering Information System (SI-ON) to support the digitalization of credit administration services and potentially improve the quality of banking credit services. The research employed the Waterfall system development method, consisting of problem identification, literature review, data collection, system requirements analysis, system design, expert validation, and research report preparation. The system was designed using Unified Modeling Language (UML), Entity Relationship Diagram (ERD), and user interface design techniques. The results indicate that the SI-ON application was successfully designed with key features including notary order management, work status monitoring, digital document management, activity history tracking, and reporting. Expert validation results showed a feasibility score of 87.08%, categorized as very good. Furthermore, the credit administration support aspect achieved a score of 88.50%, while the service quality support aspect based on the SERVQUAL dimensions obtained a score of 87.00%. The findings suggest that the proposed web-based SI-ON application is feasible and has the potential to support the digitalization of notary ordering processes, improve the effectiveness of credit administration, and enhance the quality of banking credit services.